Household decision making and resilience: Concepts and measurement approaches - Theis, Sophie; Seymour, Greg (2018)
Sophie Theis and Greg Seymour POLICY SEMINAR Addressing gender and social barriers to resilience: Measuring and leveraging household decision making for resilience Co-Organized by IFPRI and Mercy Corps JUN 27, 2018 - 09:30 AM TO 11:00 AM EDT